An Analysis of Picky Eater Towards Growth and Motor Development at Kebasen District Health Centre - Ell Khaq, Arrina; Yuniastuti, Ari; Ratna Rahayu, Sri (Universitas Negeri Semarang, 2018)
The risk of malnutrition is caused by several factors, one of which is food disruption (picky eaters). Picky Eater can be interpreted as a child with several criteria for eating behavior such as feeling full quickly, eating slowly, fussy and picky about food, lacking response and not enjoying eating. Picky eater's prevalence is quite high in the world, including Indonesia which was as much as 45.5% (2010), an increase of 77% in 2012 and 35.4% in 2016. Picky eater has a risk twice as big as being underweight at age 4, 5 years compared to nonpicky eater. Underweight will interfer motor development, intelligence, learning processes, susceptibility to infection, disease severity and mortality. The aim of the study was to analyze picky eater on toddler’s motor growth and development in the Kebasen District Health Center. This type of research was analytic with cross sectional approach. The populations in this study were all toddlers aged 12-59 months who participated enrolled in the Kebasen District of Banyumas Regency, had growth chart and join with Maternal and Child Health Service (Posyandu). The samples were 101 respondents with clustering random sampling technique followed by simple random sampling. The Chi-Square test results show there is a picky eater effect on the growth of toddlers with p-value 0.034 <0.05; and there is the influence of picky eater on motor development p-value 0.024 <0.05. Picky Eater's conclusions affect the growth and development of toddlers’ motor.